Albania and Kosovo-Albania Immigrants' Perceptions of Mental Well-Being and the Psychological Challenges Faced in Malaysia - Thartori, Voltisa; Hisham Ismail, Nik Ahamd (2024)
Background: Immigrants who relocate to a foreign country often face numerous stressors and challenges as they try to assimilate to a new culture. This transition can often have a significant impact on their mental well-being. In this qualitative study, we aim to explore and examine the life experiences of 16 Albanian and Kosovo-Albania immigrants who have settled in Malaysia, as well as those who previously resided in Malaysia but are now living in Australia and Albania. Objectives: This study aimed to investigate two main objectives: (i) to explore immigrants’ psychological prob lems and how they perceive and approach mental well-being; and (ii) to identify the challenges and barriers that immigrants face in Malaysia. Methods: The data was obtained using a qualitative phenomenological case study, using in-depth semi-structured interviews. The interviews were audio-recorded, transcribed, and thematically analysed. Results: The study’s findings indicate that immigrants’ mental well-being is positively affected by inner peace, happiness, fulfilling family needs, a balanced life, and self-improvement. On the other hand, challenges related to visa and employment pass issues, difficulty in securing employment status, feeling like a foreigner, and lack of family support have a negative impact on their mental well-being. Implications: The study’s findings advocate for targeted support programmes to address the psychological challenges of Albanian immigrants. Prioritising inner peace and self-improvement benefits their mental well-being. Policymakers are encouraged to prioritise reducing employment pass difficulties and fostering an inclusive job market to improve employment opportunities for this community.